A Critical Review Of The Effectiveness Of Teaching And Learning In Higher Education - Zanyar Nathir Ghafar; Ayu Lestari (Al-Makki Publisher, 2023)
The process of teaching and learning may be characterized as the transfer of skills from teachers to pupils. The process through which a teacher identifies and establishes the learning objectives, develops instructional materials, and puts the teaching and learning approach into action is referred to as a combination of several aspects. However, learning is a crucial component that an educator has to take into account. The purpose of this article was to review pedagogy, inclusive practices, and numerous academic publications in order to evaluate the efficacy of teaching in higher education. The study's goal is to evaluate how well professors educate in a higher education environment. The study analyzed the theory with the use of literary forms and experimental research methodologies (mainly introspection), reinforcing the practice with university experiences. The results of the research point to the introduction of role-playing and the provision of constructive and appropriate exploratory and feedback for growth as having a profoundly good effect on students' confidence and self-esteem. Additionally, it was shown that an inclusive environment fosters inclusiveness and enhances student and teacher academic achievement. The results of the study will make it possible for teachers to assist in developing and implementing an inclusive teaching and learning environment in order to raise learners' expectations and academic achievement.